Morphological and Developmental Features of Stone Cells in Eriobotrya Fruits - Lin, Shoukai; Lin, Dahe; Wu, Bisha; Ma, Shiwei; Sun, Shengfeng; Zhang, Ting; Zhang, Wenting; Bai, Yunlu; Wang, Qiong; Wu, Jincheng (Frontiers in Plant Science, 2022)
Some members of Rosaceae family, particularly pears, contain stone cells in their fruits. Although stone cells are well studied in pears, relatively little attention has been given to loquat stone cells. Only a few reports have suggested a relationship between stone cell traits and storage and transport tolerance of loquat fruits. Previously, we produced the hybrid variety JT8 from the interspecific hybrid of the loquat cultivar Jiefangzhong (JFZ) (Eriobotrya japonica Lindl. cv. Jiefangzhong, female parent) and wild Taiwanese loquat (TL) (E. deflexa Nakai, male parent). The JT8 fruits had a granular feel, similar to that of pears, due to the presence of stone cells. In this study, the shape, size, development and distribution dynamics of stone cells of Eriobotrya plants were thoroughly investigated. The results showed that loquat stone cells are brachysclereids, and often have typical branching pits. Loquat stone cells were distributed as both single stone cells and stone cell clusters (SCCs), and the density of the stone cells near the core was higher than that near the peel. Stone cell density first increased and then decreased during fruit development. These traits noted in Eriobotrya were very similar to those observed in pear, indicating a close relationship between loquat and pear. Moreover, the contents, density dynamics and aggregation traits of stone cells of the interspecific hybrid JT8 were derived from the male parent (TL). Transgressive segregation was likely exhibited in the content of stone cells and the size of the SCCs. More specifically, the content of stone cells reached 1.61% (w/w); In extreme cases, SCCs of JT8 exceeded 1000 μm in length and 500 μm in width. This demonstrated that stone cell traits could be transmitted from parent to progeny in interspecific hybridization. The density dynamics of stone cells in two loquat cultivars with different storage and transport tolerances were also investigated, which indicated that the cultivar with more stone cells was more tolerant to storage and transport. We suggest that wild loquat genetic resources containing stone cells in Eriobotrya plants can be used to gradually improve the storage and transport tolerance of loquat fruits.